Mobile genetic elements encoding antibiotic resistance genes and virulence genes in Klebsiella pneumoniae: important pathways for the acquisition of virulence and resistance - Han, Bin; Feng, Chunlin; Jiang, Yuan; Ye, Caihong; Wei, Yueshuai; Liu, Jinbo; Zeng, Zhangrui (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is an opportunistic pathogen primarily associated with nosocomial infections, characterized by a propensity for multi-drug resistance and the potential evolution into hypervirulent strains. Based on its phenotypic and genotypic characteristics, K. pneumoniae can be classified into two types: classical K. pneumoniae (cKP) and hypervirulent K. pneumoniae (hvKP). The spread of mobile genetic elements (MGEs) in K. pneumoniae has led to the emergence of carbapenem-resistant K. pneumoniae (CRKP) and carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP). The emergence of CR-hvKP is particularly concerning due to its multidrug resistance, high pathogenicity, and increased transmissibility. This review summarizes the types of MGEs present in K. pneumoniae, the mechanisms of horizontal gene transfer (HGT) mediated by these mobile elements, their roles in the dissemination of antibiotic resistance genes (ARGs) and virulence genes, and the relationships among MGEs that resemble Russian dolls or exhibit hybrid characteristics. Additionally, the clinical treatment and epidemiological characteristics of CR-hvKP are discussed. Given the high variability and transmissibility of MGEs, continuous monitoring and control of the variation and transmission of such genetic material in K. pneumoniae should be prioritized.